Altered Bcl-2/Caspase signaling and hypoxia-induced apoptosis in primary human aniridia limbal stromal cells, in CoCl2 mediated hypoxic stress, in vitro - Shanhe Liu; Shuailin Li; Shao-Lun Hsu; Fabian N. Fries; Zhen Li; Swarnali Kundu; Berthold Seitz; Maryam Amini; Shweta Suiwal; Julia Zimmermann; Simon Trusen; Tanja Stachon; et al. (PLoS ONE, 2025)
Purpose The aim of this study was to investigate apoptosis in primary aniridia limbal stromal cells (LSCs) and to assess changes in the expression of genes and proteins associated with the apoptotic pathway in response to cobalt chloride (CoCl2)-induced hypoxic stress, in vitro. Methods Primary human limbal stromal cells were isolated from the limbal region of both aniridia (AN-LSCs; n = 8) and healthy (LSCs; n = 8) donors. The cells were treated with 0 µM, 50 µM, and 75 µM CoCl2 for 48 hours. Apoptosis in each group was assessed by Flow cytometry (FC). The expression levels of apoptosis-related genes, including CASP 3/7/8/9/10, BCL2, BID, BAX, CDKN1A (p21), CDKN1B (p27), TNFα, XIAP, and BIRC5 (Survivin), were measured by qPCR. Protein level of these markers was analyzed by FC. TNFα protein expression in the supernatant was quantified using ELISA. Results Flow cytometry analysis revealed a significantly higher apoptosis rate in AN-LSCs compared to LSCs (p < 0.0001). In AN-LSCs, treatment with 75 µM CoCl₂ further increased the apoptosis rate compared to untreated AN-LSCs (p = 0.047). BCL2 mRNA levels (p = 0.0291), Caspase-8 (p = 0.0341), Caspase-10 (p = 0.0085), Bcl-2 (p = 0.0014), XIAP (p = 0.0003) and Survivin (p = 0.0074) protein levels were significantly higher in LSCs than in AN-LSCs. Conversely, Caspase-3 (p = 0.0366), Caspase-9 (p = 0.0354), p21 (p = 0.0003), and p27 (p = 0.0164) protein levels were significantly higher in AN-LSCs than in LSCs. In LSCs, exposure to 75 µM CoCl₂ led to a reduction in BCL2 mRNA (p = 0.0102) and protein levels (p = 0.0484), accompanied by an increase in CDKN1B mRNA level (p = 0.0265). In AN-LSCs, 75 µM CoCl₂ treatment resulted in a decrease in CASP3 (p = 0.049), CASP7 (p = 0.041) and BCL2 (p = 0.0218) mRNA and Bcl-2 protein levels (p = 0.0405) and an increase of TNF-α protein levels in the cell culture supernatant (p = 0.0251). Conclusions The apoptosis rate of LSCs from patients with congenital aniridia is higher than that of the control group, accompanied by alterations in multiple apoptosis-related markers. Additionally, CoCl₂-induced hypoxic stress further increases apoptosis in AN-LSCs and leads to changes in the expression of Caspase 3, Caspase 7, Bcl-2, and CDKN1B (p27). Further research is needed to elucidate the potential therapeutic targets in AAK, with the aim of preventing or slowing the progression of aniridia-associated keratopathy.